The Nationalism of Javanese Muslim Clerics: Study on Nationalism Discourse of Kitabs by Kiais of North Coast of Central Java in the XIX-XX Centuries - Muhamad Jaeni (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2020)
Treasures of the Javanese Muslim clerics (Kiais) thought on nationalism contained in their books have made a valuable contribution in maintaining Indonesia as a unitary state. Their papers discuss not only religious issues but also the values of nationalism. This study is aimed at examining the linguistic dimensions, the praxis-discourse, and the socio-cultural-political aspects of their books. It incorporates both critical discourse analysis and content analysis. From the profound analysis, the study concludes that, first, the texts concerning nationalism in a number of the Kiais’ books can be seen through their linguistic dimension. These linguistic dimensions are partly found in the books written by Kiais from coastal areas. Second, at the level of praxis-discourse, those books are mostly written in Pegon script. The preservation of Arabic Pegon is meant not only to facilitate Javanese society in learning but also to indicate the Kiais' love of the local language, which is part of the national identity. Third, those books were mostly written during the struggle of the Indonesian people against the colonizers. While writing and teaching their religious texts, the pesantren Kiais instill values of the importance of loving and caring for the motherland.